Isolasi Senyawa Triterpenoid dari Ekstrak Etil Asetat Pirdot (Saurauia vulcani. Kurth) - Boima Ramses Situmeang; Achmad Rante Suparman; Murtihapsari kadarusman; Apriani sulu parumbak; Tati Herlina (Jurnal Kimia Valensi, 2018)
Pirdot plant(Saurauia vulcani. Kurth)is a plant that grows naturally in a tropical climate. During this decoction pirdot leaves plants are used by the people to treat diabetes disease. The purpose of this study was to isolate triterpenoid compound from ethyl acetate extract of pirdot leaves. The sample extraction was performed by total of maceration method using ethyl acetate as a solvent. The separation and purification of the compound was carried out by column chromatography method followed by stain pattern analysis with thin layer chromatography (TLC). Structure characterization of pure compound was determined using UV, IR, 1H-NMR, 13C-NMR, DEPT 135º, HMQC, HMBC, 1H-1H COSY and MS spectroscopies including compared with various literatures. Based on the analysis result, the pure isolate obtained was identified as a pentacyclic triterpenoid compound, 3-hydroxy acid, 12(13)-en,28-oleanolate acid with the molecular formula C30H48O3. The triterpenoid compound of pentacyclic oleanolic acid is the first reported from the pirdot plant (Saurauia vulcani. Kurth).